Pathogenesis of acephalic spermatozoa syndrome caused by PMFBP1 mutation - Huaqiang Xia; Juan Zhang; Wuyuan Mao; Kangle Yi; Teng Wang; Lingyan Liao (Basic and Clinical Andrology)
Abstract Background Acephalic spermatozoa syndrome is a rare but severe type of teratozoospermia. The familial trait of acephalic spermatozoa syndrome suggests that genetic factors play an important role. However, known mutations account for only some acephalic spermatozoa syndrome patients, and more studies are needed to elucidate its pathogenesis. The current study aimed to elucidate the pathogenesis of acephalic spermatozoa syndrome caused by PMFBP1 mutation. Results We identified a homozygous splice site mutation (NM_031293.2, c.2089-1G > T) in PMFBP1 through Sanger sequencing. Western blotting and immunofluorescence analyses revealed that this splice site mutation resulted in the absence of PMFBP1 protein expression in the patient's sperm cells. We generated an in vitro model carrying the splice site mutation in PMFBP1 and confirmed, through RT‒PCR and Sanger sequencing, that it led to a deletion of 4 base pairs from exon 15. Conclusion A homozygous splice site mutation results in a deletion of 4 bp from exon 15 of PMFBP1, thereby affecting the expression of the PMFBP1 protein. The absence of PMFBP1 protein expression can lead to acephalic spermatozoa syndrome. This finding elucidates the underlying cause of acephalic spermatozoa syndrome associated with this specific mutation (NM_031293.2, c.2089-1G > T) in PMFBP1.